Carboxymethyl cellulose/diclofenac bioactive coatings on AISI 316LVM for controlled drug delivery, and improved osteogenic potential. (15th February 2020) - Maver, Uroš; Xhanari, Klodian; Žižek, Marko; Gradišnik, Lidija; Repnik, Katja; Potočnik, Uroš; Finšgar, Matjaž
Graphical abstract: Highlights: Novel carboxymethyl cellulose/diclofenac coatings on AISI 316LVM steel were prepared. Interdisciplinary analytical methods were employed to characterize the coatings. Biocompatible coatings enable controlled drug release and high corrosion resistance. Higher osteointegration rate and increased BMP2 and OMD gene expression achieved. Abstract: This work reports on the preparation and systematic testing of a novel multi-layered coating, comprised of the non-steroid anti-inflammatory drug diclofenac and biopolymer carboxymethyl cellulose. Drug release testing was performed on an Automated Transdermal Diffusion Cells Sampling System in combination with UV-VIS spectroscopy as the released drug concentration determination method. The results showed that most of the drug is released in the first six hours, whereas the overall released amount could be tailored through changes in the multi-layered coating composition. Biocompatibility tests performed on human osteoblast cells, showed cell viability improvement between 7% and 17% compared to the control sample. The expression of proteins playing important roles in extracellular matrix production and functioning was performed in order to obtain additional proof of the prepared materials' osteointegration boosting capacity. Finally, electrochemical measurements confirmed that the coatings do not influence the corrosion susceptibility of AISI 316LVM stainless steel.